Mechanics of double tucked back jump in dismount of uneven parallel bars - A. Manoni; E. Laterza (Asociación Española de Ciencias del Deporte, 2010)
Four double tucked back salto dismounts from the uneven parallel bars performed during the World Championships held in Stuttgart in1989 havebeenstudiedbymeansofcinematographic biomechanical analysis. The results show that the instant of release, for all gymnasts, followed (by 62 ms, on average), the instant when the center of mass (CM) reached its maximum vertical velocity (máx. Vy). In the last 62 msbefore release, while the CM was sweeping the last 14º rotation about the upper bar, a decrease by about 5% in the CM vertical velocity occurred. In spite of that, during that short period the gymnasts obtained, thanks to the vertical reaction impulse they elicited from the bar, as large an increase as 0.15 min the peak height of theCMduring flight. This highlights the important role of the actions performed in the instants immediately preceding release. If release had occurred 62 ms esarlier, in the instant of maximum Vy, the gymnasts' angular momentum would have been higher, allowing a faster rotation velocity. Yet, the angle swept in flight would have been larger, and the flight time slightly shorter (-1%). KEY WORDS: Biomechanics, Gymnastics, Training